ANALISIS SERVICE QUALITY BANDARA HANG NADIM BATAM MELALUI MODEL SERVQUAL - Ghazali, Ihwan; Maslan, Andi (LPPM Universitas Putera Batam, 2025)
Hang Nadim, located in Batam City, Riau Island Regency, is one of Indonesia's international airports. Due to its size and reputation as an international airport, Hang Nadim Airport has a policy that restricts access to each sector. The use and assignment of airport PAS cards are typically subject to restrictions for airport staff. The airport region is off-limits to cargo workers, airline employees, shopkeepers, and renters. The state is in charge of ensuring airport safety and security in order to protect travelers. Without authorization from the airport, it is forbidden for anybody to be in specific areas of the airport, erect impediments, or engage in any other activity that could jeopardize flight security and safety